2020
DOI: 10.1021/acsptsci.0c00179
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Approved Antiviral Drug in an Orally Administrable Nanoparticle for COVID-19

Abstract: There is urgent therapeutic need for COVID-19, a disease for which there are currently no widely effective approved treatments and the emergency use authorized drugs do not result in significant and widespread patient improvement. The food and drug administration-approved drug ivermectin has long been shown to be both antihelmintic agent and a potent inhibitor of viruses such as Yellow Fever Virus. In this study, we highlight the potential of ivermectin packaged in an orally administrable nanoparticle that cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…[45] We collected data from several nanostructures' types studied against the coronavirus cited above as nanotubes, nanorods, nanoparticles, nanostars, nanowires, nanocrystals, nanosheets, nanogels, nanospheres, nanocapsules, nanoclusters, and nanostructured lipid carriers (NLCs). Of these, were identified the following nanotechnology-based approaches: bioconjugated carboxyl quantum dots (QDs); [74] silver nanomaterials; [58,60,69,80,96,97] synthetic virus-like particles (sVLPs); [77] gold nanoparticles; [59,77] biopolymeric/biodegradable polymeric nanoparticles and hydrogels (e.g., chitosan, collagen, poly(ethylene glycol) (PEG), poly lactic-co-glycolic acid (PLGA), and poly(hydroxyethyl) methacrylate); [61,62,63,79,[85][86][87]91,93] carbon quantum dots (CQDs) [71] and cationic carbon dots based on curcumin (CCM-CDs); [68] glutathione(GSH)-capped silver-sulfide nanoclusters (GSHcapped Ag 2 S NCs); [64] gold nanorod-based heptad repeat 1 (HR1) peptide; [72] antigen and adjuvant-loaded hollow polymeric nanoparticles; [73] bovine serum albumin (BSA)-coated tellurium nanoparticles (Te/BSA NPs) with a unique triangular star shape (Te/BSA nanostars); [65] GSH-modified zinc-sulfide nanoparticles (ZnS NPs); [66] glycyrrhizic-acid-based carbon dots (Gly-CDs); [67] multi-walled carbon nanotubes (MWCNTs) with target functions; [83] metal-decorated single-wall carbon nanotubes (SWCNTs); [100] NLCs; [88] graphene oxide; [60,82,92] iron oxide nanoparticles (IONPs), [75] functionalized graphene sheets;…”
Section: Main Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…[45] We collected data from several nanostructures' types studied against the coronavirus cited above as nanotubes, nanorods, nanoparticles, nanostars, nanowires, nanocrystals, nanosheets, nanogels, nanospheres, nanocapsules, nanoclusters, and nanostructured lipid carriers (NLCs). Of these, were identified the following nanotechnology-based approaches: bioconjugated carboxyl quantum dots (QDs); [74] silver nanomaterials; [58,60,69,80,96,97] synthetic virus-like particles (sVLPs); [77] gold nanoparticles; [59,77] biopolymeric/biodegradable polymeric nanoparticles and hydrogels (e.g., chitosan, collagen, poly(ethylene glycol) (PEG), poly lactic-co-glycolic acid (PLGA), and poly(hydroxyethyl) methacrylate); [61,62,63,79,[85][86][87]91,93] carbon quantum dots (CQDs) [71] and cationic carbon dots based on curcumin (CCM-CDs); [68] glutathione(GSH)-capped silver-sulfide nanoclusters (GSHcapped Ag 2 S NCs); [64] gold nanorod-based heptad repeat 1 (HR1) peptide; [72] antigen and adjuvant-loaded hollow polymeric nanoparticles; [73] bovine serum albumin (BSA)-coated tellurium nanoparticles (Te/BSA NPs) with a unique triangular star shape (Te/BSA nanostars); [65] GSH-modified zinc-sulfide nanoparticles (ZnS NPs); [66] glycyrrhizic-acid-based carbon dots (Gly-CDs); [67] multi-walled carbon nanotubes (MWCNTs) with target functions; [83] metal-decorated single-wall carbon nanotubes (SWCNTs); [100] NLCs; [88] graphene oxide; [60,82,92] iron oxide nanoparticles (IONPs), [75] functionalized graphene sheets;…”
Section: Main Findingsmentioning
confidence: 99%
“…[88,103,104] Ivermectin is a clinically approved antiviral drug and was repurposed against SARS-CoV-2, using orally administering PLGAgrafted-PEG-maleimide nanoparticles, an amphiphilic and biodegradable block copolymer system, which was capable of delivering a more potent therapeutic dose. [87] The system demonstrated potential for the therapeutic drug to COVID-19 by multisite inhibition into decreasing the viral uptake and transmission by i) inhibition of viral spike protein level and its entry rate by downregulation of ACE2 expression, and ii) possibly, inhibition of nuclear transport activities mediated by proteins (e.g., importin α/β1 heterodimer). [87] A recent study hypothesized that excessive neutrophil extracellular traps (NETs) and extracellular DNAs (eDNAs) could activate NETosis, neutrophil-specific programmed cell death might be associated with COVID-19 pathogenesis.…”
Section: Nanomaterials and The Novel Sars-cov-2: Recent Advances To Reduce The Spread Of Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Nanomaterial-Ivermectin composites have been shown to enhance protective efficacy and long term stability in the blood against Zika virus in vitro [59] . Recently, a study concluded the stability of non-immunogenic nanoparticles combined with ivermectin, tagged with immunoglobulin fragment (orally fed) as the treatment and prevention against SARS-CoV-2 [60] . However, the in vivo safety and biodegradability of nanomaterials after being exposed to lung epithelia warrant more research focus.…”
Section: Ivermectin and Covid-19mentioning
confidence: 99%